PENERAPAN MODEL THINK PAIR SHARE (TPS) PADA PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR NEGERI 274/VI MUARA DELANG KABUPATEN MERANGIN PROVINSI JAMBI - Muhammad Arvi; Mansurdin; Leni Zahara; Hamimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aims to describe the improvement of fifth-grade students' learning outcomes in Natural and Social Sciences (IPAS) through the application of the cooperative learning model Think Pair Share (TPS) at SDN 274/VI Muara Delang, Merangin Regency, Jambi Province. The background of this study is the low learning outcomes of students, most of whom had not reached the Learning Objective Achievement Criteria (KKTP), caused by a monotonous, teacher-centered learning process. This research used a classroom action research design carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were the fifth-grade teacher and 27 students. Data were collected through observation, tests, and interviews, then analyzed using both quantitative and qualitative approaches. The results show that the teaching module assessment increased from 87.50% (Good) in Cycle I to 96.43% (Very Good) in Cycle II. Teacher and student activity both increased from 87.50% to 95.00%. Students' learning outcomes also improved, with the average score rising from 73.08 (Low) in Cycle I to 88.59 (Good) in Cycle II. It is concluded that the application of the Think Pair Share (TPS) model effectively improves fifth-grade students' learning outcomes in IPAS.